Social Conflict Dynamics in Non-Procedural Hajj Practices in the Bangka Belitung Islands - Akbar Farid; Muhammad Hayyi' Lana Alkhan; Muhammad Yogie Adha (Indonesian Center for Religion and Society Studies (InTReSt), 2025)
The phenomenon of non-procedural Hajj in the Bangka Belitung Islands represents a complex form of social conflict between state policy, the economic interests of travel agencies, and the spiritual motivations of the community. This study aims to understand the structural, cultural, and behavioral dimensions of non-procedural Hajj practices through a descriptive qualitative approach. Data were collected through in-depth interviews with six informants consisting of religious officials, licensed travel agency managers, and non-procedural pilgrims, then analyzed using Johan Galtung's triangle of conflict model (Contradiction, Attitude, Behavior). The results show that the conflict surrounding non-procedural Hajj stems from structural inequalities in quota policies and Hajj bureaucracy, reinforced by cultural legitimacy that places religious intentions above administrative rules, and manifested in social behavior that maintains practices outside the legal corridor. Theoretical analysis confirms that structural and cultural violence operate simultaneously, creating an illusory negative peace. This study emphasizes the need for policy transformation and social awareness towards positive peace through religious education, inclusive regulation, and value-based social mediation.